Chromate Formed in a Trivalent Chromium Conversion Coating on Aluminum. Issue 7 (13th June 2017) - Qi, J.; Gao, L.; Liu, Y.; Liu, B.; Hashimoto, T.; Wang, Z.; Thompson, G. E.
Abstract : This present study employs aluminum substrates to investigate the formation of Cr(VI) species during a trivalent chromium conversion coating process. The study had a particular focus on understanding the influences of copper in the substrate and O2, ZrF6 2− and F − in the bath on the formation of Cr(VI) species, which were detected by Raman spectroscopy. Comparison of electropolished aluminum and sputtering-deposited aluminum substrates revealed greatly increased rates of coating growth associated with an enrichment of copper impurity in the electropolished substrate that was revealed by transmission electron microscopy. With respect to chromium chemistry in a developed coating, the presence of dissolved oxygen and long conversion treatment times promoted the formation of Cr(VI) species that are generated by oxidation of Cr(III) species. The Cr(III) species are oxidized by H2 O2, which was produced by oxygen reduction reaction. The generation of H2 O2 was demonstrated by analysis of the treatment bath using UV spectrophotometry.